Polemik Qirā’ah Sab’ah Antara Zamakhsharī dan Abū Ḥayyān - Nawawi, Fuad (SUHUF, 2021)
This paper shows that traditions, socio-cultural networks, ideologies, and interests formed a perspective on knowledge, including knowledge of qirā’āt sab’ah (seven methods of reading the Qur’an). Az-Zamakhsyarī (d. 538 H / 1143) is critical to qirā’āt sab’ah. It is because he has a Mu’tazila background who considered that some of the various readings of qirā’āt sab’ah are the products of scholarly ijtihad. Mu’tazila also thinks that not all qiraah sab’ah is part of the Qur’an. Az-Zamakhsyarī was also sided with the nahwu Basrah school which positions language rules as the decisive “judge”. If there is a qira’ah that is not in accordance with the rules, the qira’ah is punished as a syāz qira’ah (weird reading). On the other hand, Abu Hayyān (d. 745 H/1344) defended qirā’āt sab’ah because Abū Hayyān had an Ash’ariyyah background. This theological school views qirā’āt sab’ah as qira’ah mutawatir (trusted reading) so it is considered taboo to be criticized. Abū Hayyān was sided with the nahwu school of Kufa which judged that anything derived from Arab expressions—not to mention qirā’āt sab’ah—was accepted as a source of language, even though at first it differed from the general rule